(untitled) (Fiep Bulletin - online, 2014)
Abstract: The teachers’ of the initial formation pedagogic practice in physical education, especially the evaluation process, presents private characteristics in agreement with the axis curricular in that act and the cycle of professional development in that meet. In that perspective, this investigation analyzed the characteristics of the evaluations practices implemented by the teachers of the initial formation, according to the axis curriculars that acted and the current development cycle. The participants consisted of college career’s teachers from superior teaching that supplied classes in the course, in the school period of the year of 2005, in the course of physical education of Unioeste. The instruments used in the data collection they consisted of documental analysis, that it includes the teachers’ annual teaching plans, as well as of semi-structured interview. For the analysis of the data, the teachers were contained considering the axis curriculars and the cycles of professional development. In what this refers to the cycles of professional development and the relationship with the evaluation tendencies that orientate the evaluations practices, the predominance of college teachers of the diversification cycle was observed in the tendency humanist and of the cycle of stabilization in the traditional tendency of evaluation, presenting divergences in the evaluation process, specifically in the conception, in the objectives and in the procedures used to evaluate. However, it was verified high association level and similarity of the evaluation process developed by the teachers that act in the same axis curriculars. The college teachers, which belonged to the axes biodinamic, technician-functional and scientific technological, presented the system of suitable evaluation with the traditional tendency of evaluation. In compensation, the teachers, which belonged to the axes partner-anthropological, pedagogic and behaviour, they presented characteristics of the progressive tendency of evaluation. Already the cultural axis, that pondered the largest number of subjects, they assisted through the evaluation system that implemented the traditional tendency so much with relationship the humanist-reformista of evaluation.